191k views
4 votes
Written as a simplified polynomial in standard form, what is the result when

(x + 1)2 is subtracted from 7x2 - 4x + 6?

User Silx
by
4.8k points

1 Answer

4 votes

Answer:

The resultant polynomial is:
6x^2-6x+5

Explanation:

We need to subtract
(x+1)^(2) from
7x^2-4x+6

so, we start by performing the multiplication involved in the perfect square of the binomial
(x+1), and obtain its expression in separate terms that can be combined:


(x+1)^(2)=(x+1)\,(x+1)=x^2+x+x+1=x^2+2x+1

Now we can subtract this trinomial from
7x^2-4x+6, and combining like terms to get the resultant polynomial expression:


7x^2-4x+6-(x^2+2x+1)=7x^2-4x+6-x^2-2x-1=7x^2-x^2-4x-2x+6-1=6x^2-6x+5

Then the resultant polynomial is:
6x^2-6x+5

User Ktzr
by
5.1k points